The influence of academic background Knowledge on the English Language Proficiency Level of advanced students at the Foreign Language Department of the University of El Salvador, year 2015. - De León González, Cecilia Guadalupe; Ortiz Castro, Marvin Ernesto; Salguero, Fátima Gabriela; Carranza Campos, Miguel Ángel; Landaverde, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
It is widely known that the extent to which students learn new content depends on factors such as the skill of the teacher, the interest of the student, and the complexity of the content itself. What students already know about a content is one of the strongest indicators of how well they will learn new information related to that content. According to Robert J. Marzano, (2004) in his book titled “Building Background Knowledge for Academic Achievement” there are some scenarios that demonstrate the dramatic impact of academic background knowledge on success in school. Students who have a great deal of background knowledge in a given subject area are likely to learn new information readily and quite well. The terms background knowledge and prior knowledge are generally used interchangeably. For purposes of the present study, Academic Background Knowledge (ABK) is understood as a combination of the learner's preexisting attitudes, experiences, and knowledge of a specific subject acquired during previous academic years plus socioeconomic status, that combines parents´ educational level, occupational status and income level. In this regard, Academic Background Knowledge is different from other background knowledge terms. It is important to know that Academic Background Knowledge is a factor which plays a role to achieve successfully a second language , in this particular case, on advanced English students from the Foreign Language Department; that is why, any students in the English classes have a level of ABK. For that reason, this research tries to identify the levels of ABK from advanced English students in order to correlate it with their English language proficiency. The purpose of this research is to identify the influence of Academic Background Knowledge (ABK) on the English Proficiency level of advanced students from the Foreign Language Department; for that reason, several techniques have been applied: a survey and a placement test were administered in order to collect the data that is needed to identify those factors that affect students when learning a new language, and then the data collected was analyzed by the researchers with the help of Statistical Package for the Social Sciences (SPSS).
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador 2016
Bibliografía : hojas 69-70
Audiencia general.
Keywords: The factors that influence the acquisition of a second language